Buyer and Seller Satisfaction in E-Commerce Growing Digital Marketplace in Hyderabad (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The rapid growth of e-commerce has transformed the buying and selling landscape, particularly in urban hubs like Hyderabad, Telangana. This study investigates the satisfaction levels of buyers and sellers engaged in e-commerce platforms, focusing on factors such as user experience, trust, product quality, and customer support. Through surveys and interviews with a diverse group of participants, the study identifies key determinants that influence satisfaction on both ends of the transaction. The findings reveal that while buyers prioritize competitive pricing, product authenticity, and timely delivery, sellers are more concerned with platform fees, marketing support, and fraud prevention mechanisms. The study also highlights the role of technology adoption, localized customer preferences, and challenges such as logistical inefficiencies and trust deficits in shaping the overall satisfaction of stakeholders. This research contributes to a better understanding of Hyderabad's e-commerce ecosystem and offers actionable insights to enhance buyer-seller experiences.